非目的语环境下汉语课堂学习焦虑调查：以马来西亚非华裔生为例 - Ting Hie Ling; Chong Pei Qi (Universitas Negeri Malang, 2022)
本文采用Horwitz等人（1986）设计的外语学习焦虑量表， 简称FLCAS （Foreign Language Classroom Anxiety Scale）作为研究工具，对非目的语环境下学习汉语的221名非华裔生进行汉语课堂学习焦虑研究。此221名非华裔生均来自马来西亚砂拉越玛拉工艺大学选修《基础华语》课的学习者。在问卷收集完善后，采用SPSS 22.0作为数据统计工具，对非华裔生的汉语学习焦虑程度、汉语学习焦虑三个维度与性别差异进行数据分析。分析结果显示，非华裔生在汉语课堂普遍经历学习焦虑。通过独立样本T检验结果发现，非华裔生汉语课堂学习焦虑与性别差异的相关性并不显著。 This study adopted Foreign Language Classroom Anxiety Scale (FLCAS) designed by Horwitz et al (1986) to determine Mandarin as foreign language learning anxiety among 221 non-native Mandarin learners in non-target language context. These 221 non-native Mandarin learners were those who enrolled in Introductory Mandarin Language course from University Teknologi MARA, Sarawak Branch. SPSS 22.0 was employed to analyze the data such as non-native Mandarin learners’level of anxiety and gender differences. Findings from this study revealed that non-native Mandarin learners are at moderate level of anxiety. Results from independent T-test analysis shows that there were no significant differences between learners’ level of anxiety and gender.